Trimethylamine-N-oxide and cerebral stroke risk: A review - Phurbu Dolkar; Tenzin Deyang; Nikhilesh Anand; Annan Gopinath Rathipriya; Tousif Ahmed Hediyal; Vichitra Chandrasekaran; Naveen Kumar Krishnamoorthy; Vasavi Rakesh Gorantla; Muhammed Bishir; Luay Rashan; Sulie L. Chang; Meena Kishore Sakharkar; et al. (Neurobiology of Disease, 2024)
Trimethylamine-N-oxide (TMAO) is a gut microbiota-derived metabolite produced by the action of gut microbiota and the hepatic enzyme Flavin Mono‑oxygenase 3 (FMO3). TMAO level has a positive correlation with the risk of cardiovascular events, including stroke, and their level is influenced mainly by dietary choice and the action of liver enzyme FMO3. TMAO plays a role in the development of atherosclerosis plaque, which is one of the causative factors of the stroke event. Preclinical and clinical investigations on the TMAO and associated stroke risk, severity, and outcomes are summarised in this review. In addition, mechanisms of TMAO-driven vascular dysfunction are also discussed, such as inflammation, oxidative stress, thrombus and foam cell formation, altered cholesterol and bile acid metabolism, etc. Post-stroke inflammatory cascades involving activation of immune cells, i.e., microglia and astrocytes, result in Blood-brain-barrier (BBB) disruption, allowing TMAO to infiltrate the brain and further aggravate inflammation. This event occurs as a result of the activation of the NOD-like receptor family pyrin domain containing 3 (NLRP3) inflammasome pathway through the release of inflammatory cytokines and chemokines that further aggravate the BBB and initiate further recruitment of immune cells in the brain. Thus, it's likely that maintaining TMAO levels and associated gut microbiota could be a promising approach for treating and improving stroke complications.